Cognitive profile and frailty in patients with idiopathic normal pressure hydrocephalus - Dejgaard, Magnhild S.; Eide, Per Kristian; Tangen, Gro Gujord; Skovlund, Eva; Selbæk, Geir; Wyller, Torgeir Bruun (Frontiers in Neurology, 2025)
BackgroundCognition and frailty are sparsely studied in patients with idiopathic normal pressure hydrocephalus (iNPH). We aimed to describe the preoperative cognitive function compared with normative data and frailty profile in iNPH patients accepted for shunt surgery.MethodsAll patients were diagnosed according to international guidelines and underwent a standardized cognitive and physical examination and a geriatric assessment prior to surgery. Z-scores for the cognitive tests were calculated based on age and education adjusted population norms.ResultsThe study cohort included 276 iNPH patients accepted for shunt surgery. Mean ± SD age was 73.1 ± 5.7 years, education 12.5 ± 3.8 years, and 61% were male. The median (IQR) score on the Mini-Mental State Evaluation was 27 (24–29), and the median (IQR) Clock Drawing test score was 4 (3–5). Mean (SD) z-score for immediate verbal recall was −1.74 (0.98), for delayed recall −1.66 (1.01), for figure copying −0.85 (1.35) for Trail Making Test A -1.50 (1.09), for Trail Making Test B −1.88 (1.03), for phonemic fluency −1.46 (1.10), and for semantic fluency −1.59 (1.20). Cluster analysis identified three groups, mainly differing regarding visuospatial function. The mean (SD) Frailty Index score was 0.23 (0.13), indicating mild frailty. The frailty domain most affected was physical function.ConclusioniNPH patients showed reduced cognitive function across all domains. The patient group is rather heterogeneous regarding cognitive symptoms, and no specific cognitive profile was identified. Cognitive assessment offers limited utility for diagnosing a typical pattern specific for iNPH but is important due to the complex needs for this patient group. Whether cognitive and frailty profile can be used to identify shunt responders, must be assessed in longitudinal studies.